PENGARUH BUDAYA ORGANISASI DAN PERSEPSI DUKUNGAN ORGANISASI TERHADAP KOMITMEN KARYAWAN - Ghita Sandra; Amalia Alfian; Zulkarnain n (Universitas Negeri Makassar, 2015)
The purpose of this study is to investigate the influence of organizational culture and perceived organizational support toward organizational commitment. The instrument was used in this study were organizational commitment scale is based on aspects of organizational commitment, organizational culture scale is based on aspects of organizational culture and perceived organizational support scale based on aspects of the perceived organizational support. This study was involved 203 banking employees. The results showed that organizational culture and perceived organizational support significantly influenced of organizational commitment. It means organizational culture and perceived organizational support contributed to increasing organizational commitment. Meanwhile, organizational culture has a greater contribution to organizational commitment than perceived organizational support. This study also showed that two aspects of organizational culture contributed to organizational commitment, there were espoused values and artifacts. An espoused value has a higher contributed to organizational commitment. Meanwhile, for perceived organizational support, fairness aspect contributed to organizational commitment.